ANALISIS PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA APARAT PEMERINTAH DAERAH DENGAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERATING - Kristiani, Yesi; Mokhlas, Mokhlas; Sukanto, Eman (Stability: Journal of Management and Business, 2018)
Indonesia is a country with more than 250 million people, spread over thousands of islands stretching from Sabang Island to Irian Jaya Island. Residents in their quest for a better life, will migrate to other islands. This actual condition becomes a great opportunity for telecommunication companies through mobile operators to gain profit. Various innovations are made and offered to users with different purposes and approaches. The consumer himself is a very distinctive person and carries his identity as part of a tradition. They will carry the identity of that tradition and culture along with its migration. In kehidpannya, humans need a communication channel in the form of mobile operators in accordance with the style and personal characteristics. This study aims to determine the influence of cultural factors on the purchase decision of prepaid cell phone prepaid card. The research method used in this research is correlation method, with multiple regeresi analysis tool and processed by using SPSS 2017. This research use sample with 95 kuisinoner which can be used. Based on the results of regression with t test and F test can be concluded that cultural factors have a positive and significant impact on the purchase decision process prepaid prepaid card, while the results of F test, indicate that cultural factors and social factors together positively influence the purchase decision consumer.